Production and dissemination of nursing research - Maria Vera Lúcia Moreira Leitão Cardoso (Rev Rene)
The dissemination of researches performed by nurses has increased significantly, when analyzed through the prism of the historical process that characterizes the evolution of Nursing as a science. Part of the number of studies published in journals, whether national or international, comes from the results of theses and dissertations developed in several areas that compose the Nursing's body of knowledge. However we still have a lot to evolve, especially concerning the impact, the effective contribution of theses researches for the improvement of the profession in a greater context. We need to pay attention to the rigor that the scientific method requires, for the development of evidence-based studies, so they clarify and document the skills of those who bring together Nursing, considering its specificity of human care, in the amplitude of political, academic, scientific and healthcare dimensions.